Barriers and facilitators for the provision of radiology services in Zimbabwe: A qualitative study based on staff experiences and observations. - Saba Hinrichs-Krapels; Lazarus Tombo; Harriet Boulding; Edith D Majonga; Carole Cummins; Semira Manaseki-Holland (Public Library of Science (PLoS), 2023)
Despite its fundamental role in diagnostic and curative care, radiology has been described as a neglected essential service in many low and middle-income countries (LMICs). Previous studies have demonstrated basic equipment and infrastructure shortages in LMIC settings, but no studies to date have gone further in understanding the perceptions and experiences of staff delivering radiology services, as a way of identifying their perspectives on barriers and facilitators for delivering services, and the potential for where improvements can be made. Our qualitative study aimed to: (a) identify barriers for delivering radiology services, and (b) suggest potential facilitators for improvement of radiology service delivery in the Zimbabwean context; from the perspective of radiology staff. We conducted semi-structured interviews (n = 13) and three focus groups (n = 24 radiographers), followed by four half- to full- days of field observations to validate insights from the interviews and focus groups in all three public hospitals and one private hospital in the Harare metropolitan area. Our study identified four main barriers for delivering radiology services: (i) poor basic infrastructure, equipment, and consumables; (ii) suboptimal equipment maintenance; (iii) shortage of radiology staff and skills development; and (iv) lack of wider integration and support for radiology services. We also identified a strong sense of motivation among staff to keep radiology services, pointing to what may be an enabler and facilitator for improving radiology services. These findings point to potential risks to patient safety and quality of delivering radiology services. More importantly, we found a strong sense of personal motivation displayed by the staff, suggesting there is the potential to maintain and improve existing practices, but this would require investments to train and remunerate more radiology staff, as well as investing in continuing professional development.